A 50-Million-Year-Old Fossil Forest from Strathcona Fiord, Ellesmere Island, Arctic Canada: Evidence for a Warm Polar Climate - Francis, Jane E. (ARCTIC, 1988)
The remains of a fossil forest are buried within a sedimentary sequence of Eocene age (approximately 50 million years old) near Strathcona Fiord, Ellesmere Island. Large petrified tree stumps are preserved in their original growth positions in coals of the Eureka Sound Group, a sequence of sandstones, siltstones and coals deposited in a delta/floodplain environment. The dimensions of 83 stumps were recorded and their positions plotted on a plan of the exposed area of coal. The fossil stumps are roughly conical in shape, up to 1.8 m high and with roots spreading up to 5 m in diameter. They are closely spaced on the coal, some only 1 m spart. A density of 1 stump in 27 sq. m (367 stumps/Ha) was calculated for this forest. The stumps represent large forest trees that grew in freshwater, swampy conditions between large river channels. Their buttressed roots provided extra support in the waterlogged peats. The rivers periodically shifted their courses, flooding the forest and burying them under silts and sands. Wide growth rings in the fossil wood, in addition to evidence from associated sediments and vertebrate faunas, indicate favourable growing conditions in a mild, cool/warm temperate climate with high rainfall. Palaeolatitude studies suggest that the forest lay close to its present high-latitude position during the Euocene. Such a forest is therefore evidence that the Eocene polar climate was much warmer than today and that the trees were able to tolerate polar sunlight regime of continuous summer sunlight followed by months of winter darkness.Key words: fossil forest, Tertiary, Canadian Arctic, palaeoclimate, Ellesmere Island, petrified wood, Eureka Sound Group Mots clés: forêt fossilisée, tertiaire, Arctique canadien, paléoclimat, île Ellesmere, bois pétrifié, groupe d’Eureka Sound